IDENTITI BUDAYA DALAM FILEM SERAM INDONESIA DAN MALAYSIA SEKITAR TAHUN 2000an - Muhammad Zulhisyam, Bin Mohammad (Universiti Malaysia Sarawak(UNIMAS), 2019)
This study is related to the lack of cultural identity in Indonesian horror films around the 2000s because of several factors such as focusing on profits rather than the rich content of traditional rich culture in Indonesia. As a result of this study, a short film "Suraya" was produced by applying the cultural elements practiced in Indonesia.